Simulation Study of Hot Waterflood and WASP Injection Post Mature Steamflood - Ludovika Jannoke; Iwan Setya Budi; Astra Agus Pramana (Journal of Earth Energy Science, Engineering, and Technology, 2020)
Steamflood is the most successful thermal EOR applied throughout the world and have produced the biggest portion of oil from EOR methods. As high intensity energy and associated cost are put to produce oil, optimization in any level can have tremendous impacts. Optimization in steamflood operation can be achieved by optimizing steam injection (rate, time), especially in mature pattern/ field or nearing the end of field life/ abandonment. This objective can be done thru utilization of retained heat in the reservoir and overburden/ underburden as they are not instantaneously produced with fluids. By using reservoir simulation, it can be shown that injection is not necessary to be continue until abandonment but can be stopped at a much earlier time hence a much profitable steamflood operation can be achieved.